Mother Tongue Proficiency: An Empirical Study of BPSG Students at Padmakanya Multiple Campus, Kathmandu (Research Journal of Padmakanya Multiple Campus, 2024)
Mother tongue refers to the first language that children acquire from their parents and use within their households as they begin to speak. This study investigates the knowledge of mother tongues among the students of Bachelor’s in Public Service and Governance (BPSG) at Padmakanya Multiple Campus. The study sample comprises 80 students from the 1st, 2nd, 4th, and 5th semesters, with 60 selected through stratified random sampling. A sample size of 60 out of a total population of 80 students is substantial, covering 75 percent of the population. This large sample size enhances the reliability of the results and reduces the margin of error, ensuring that the findings are likely to be representative of the entire population. Data collected from respondents were presented using tables, pie charts, and bar diagrams. Among the 60 respondents, 10 different languages were spoken as their mother tongue. Regarding proficiency, 52 students (86.67%) could listen, understand, and speak their mother tongue fluently. Some could only identify their mother tongue when spoken or understand it without being able to speak it properly. Notably, all respondents expressed a strong desire to preserve their mother tongues, demonstrating an awareness of its importance. Most respondents recognized their mother tongue as integral to their identity and cultural connection, providing them a sense of uniqueness and serving as valuable assets. The study found that while the proficiency in speaking, writing, and understanding Nepali was high, proficiency in case of other languages was less. The significance of mother tongue lies in reflecting culture, establishing personal identity, and fostering confidence. On the other hand, the major challenges of speaking, writing, and understanding other languages in contemporary era, marked by the influence of foreign languages, modernization, and migration, can be mitigated through increased awareness, the development of conducive teaching-learning environments, and prioritizing mother tongues.